Expansionist Foreign Policy of Bulgaria in the Context of the Nation-Stateization Process - IŞIK, Mustafa (CenRaPS Journal of Social Sciences, 2023)
The relationship between nation-stateization processes and foreign policy in the Balkans gained importance after the rebellion movements. The Balkan states, which wanted to establish their own nation-states, followed an expansionist foreign policy within the framework of aid from both Europe and Russia during this time. While the new Balkan states, which tried to separate from the millet system of the Ottoman Empire with revolts, put these policies in the cultural and religious background, it is seen that the state and border imaginations clashed among themselves. In this study, we will examine the expansionist nation-state foreign policy of Bulgaria in the new Balkan order that emerged after the Ottoman-Russian war. In this research, an answer will be sought to the question "Which internal and external dynamics did Bulgaria take into action while following this foreign policy?’’ It is seen that the religious and cultural motifs used by Bulgaria in the nation-stateization process are effective in the execution of foreign policy. Since the link between foreign policy and domestic policy in Bulgaria and other Balkan countries develops through nationalism, the concepts of border and ethnicity are always open to discussion. This study, which reveals that not only internal dynamics are involved in the background of the expansionist foreign policy followed by Bulgaria in the nation-stateization process, is important in terms of showing the effect of external factors.